Evaluation of suitability of CO2 geologic storage in deep saline aquifers in Lindian area of Songliao Basin - Yongfa MA; Junling DONG; Xu WANG; Lan HE; Xuejun ZHOU; Ling LIU; Guang LIU; Zhenzhen SHI; Guannan CAO; Yan LIU; Xiuhai LI; Tian LIU; et al. (Shuiwen dizhi gongcheng dizhi)
Carbon dioxide (CO2) geological storage is one of the most direct and effective measures to alleviate the greenhouse effect under the current technical conditions. Deep saline aquifers and cap beds are widely distributed in Lindian, Heilongjiang Province, offering favorable geological conditions and great potential for CO2 geological storage. However, due to the lack of oil exploration data, the high accuracy suitability evaluation has not been carried out. This study, in close alignment with the geological, economic, environmental, and other conditions, established a suitability evaluation system for CO2 geological storage. Following the principles of objectivity, comprehensiveness, focus, compatibility, and feasibility, the study decomposed 11 sub-layers of indicators and 32 evaluation indicators from the three index layers of storage safety suitability, storage potential suitability, and storage social and economic suitability, divided 5 evaluation levels. The evaluation system was applied to the deep saline aquifers of the Wuyuer Depression, Keshan−Yilong Anticline, Heiyupao Depression, and Qijia−Gulong Depression using data from geothermal exploration wells and the Analytic Hierarchy Process for a comprehensive fuzzy mathematical evaluation. The results show that the four secondary tectonic units in the study area exhibit good crustal stability. The cover layer is dominated by multiple sets of large thickness and continuous stability of argillite, while the reservoirs are all multiple sets of clastic rocks with large porosity and good permeability. These regions are not prone to geological hazards and are all suitable for CO2 geological storage, with the Heiyupao Depression being the most suitable. This study provides a scientific basis for the implementation of site selection and demonstration projects in this area.